Distal Renal Tubular Acidosis Associated With Anion Exchanger 1 Mutations in Children in Thailand - Sookkasem Khositseth (2018)
Background: Mutations in the anion exchanger 1 (AE1) gene encoding the erythroid and kidney anion (chloride-bicarbonate) exchanger 1 may result in hereditary distal renal tubular acidosis (dRTA). Hemoglobinopathies are common in Thailand. We analyzed AE1 and hemoglobin mutations in children in Thailand with dRTA to evaluate their association with clinical manifestations. Study Design: Case series. Setting & Participants: 17 patients were recruited from 6 referral hospitals in 4 regions of Thailand. Predictors: AE1 mutations were detected by means of nucleotide sequence alterations. Hemoglobin E (HbE) was detected by means of hemoglobin typing, and thalassemia, by means of analysis of globin genes. Hemolytic anemia was indicated by decreased hemoglobin and hematocrit values in the presence of reticulocytosis. Outcomes & Measurements: Leading clinical manifestations in patients were failure to thrive and muscle weakness. Compensated or overt anemia was identified in some cases. Coexistence of AE1 mutations with HbE or α+-thalassemia was present in a number of patients. Results: 12 of 17 patients (70%) carried AE1 mutations, 7 patients (41%) had HbE, and 1 patient (6%) had α+-thalassemia. Patients with AE1 mutations presented with compensated hemolysis when they had metabolic acidosis. A patient with compound heterozygous Southeast Asian ovalocytosis/G701D and heterozygous α+-thalassemia showed severe hemolytic anemia. Limitations: 5 patients (30%) without detectable AE1 mutation also were unknown for other genetic abnormalities. Conclusions: Most of the patients with dRTA studied carried autosomal recessive AE1 mutations. Metabolic acidosis, which could be alleviated by adequate alkaline therapy, induced variable degrees of hemolysis in patients with dRTA associated with autosomal recessive AE1 mutations, especially in the presence of thalassemia. © 2007 National Kidney Foundation, Inc.